Skyttea heterochroae comb. et nom. nov. (Helotiales) un hongo liquenícola propio de Pertusaria heterochroa, presente en Catalunya, Islas Baleares y Maltra - Navarro-Rosinés, Pere; Muñiz Pérez, Diana (Revista Catalana de Micologia, 2011)
Skyttea heteroehroae combo et nomo nov. (Helotiales) a lichenicolous fungus fromPertusaria heterochroa, present in Catalonia, Balearic Islands and Malta.The new name Skyttea heteroehroae combo et nomo nov. is proposed to include Lecidea pertusariieola Jatta in the genus Skyttea, in order to avoid the homonony with S. Pertusariicola Diederich et Etayo.Skyttea heleroehroae is a non-lichenized lichenicolous fungi that grows specifically on Pertusaria heleroehroa, and it is only known from few European Mediterranean localities, in concrete from Catalonia, Ibiza, Majorca and Malta. A description of this fungus based on the studied specimens is included, and its characteristics are compared with those of the related species, principally with S. Mayrhoferi and S. pertusariicola, two species that also grow on Perlusaria. Some collections of S. Pertusariicola from Catalonia have remained unnoticed, because of confusion with Unguieulariopsis thallophila, a lichenicolous fungi specific of Lecanora gr. ehlarotera.